Perancangan Sistem Informasi Penggajian Guru Pada SMK Negeri 1 Cikarang Selatan - Wahyu Hadikristanto (Jurnal SIGMA, 2021)
SMK Negeri 1 Cikarang Selatan in processing Payroll Teacher still manual by using Excel format. The problems that often arise in the payroll system in SMK Negeri 1 Cikarang Selatan is a payroll error, mismatch reports with pay slips and do not have data storage databases, therefore required adalanya a computerized information system to facilitate the data processing. The research method used in this payroll information system is a structured method, while for the system pengembaangan using prototype, the method of analysis by using tools consisting of Flowmap and DFD, data collection methods with Interviews, Observations and Library Studies. And Making this application program using Borland Delphi 7 and with MySQL database 5.0.67. Keywords: information system, payroll, payroll information system.